Estimated Glomerular Filtration Rate Is Associated With an Increased Risk of Death in Heart Failure Patients With Preserved Ejection Fraction - Chen, Zhuo; Lin, Qian; Li, Jingen; Wang, Xinyi; Ju, Jianqing; Xu, Hao; Shi, Dazhuo (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: Renal dysfunction is associated with adverse cardiovascular outcomes in patients with heart failure (HF), but its impact on patients with heart failure with preserved ejection fraction (HFpEF) remains unclear. METHODS: 3,392 subjects of the TOPCAT (Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist) trial were assigned to two groups by estimated glomerular filtration rate (eGFR) ≥ 60 ml/min/1.73 m² or 30-59 ml/min/1.73 m². The outcomes, including all-cause death, cardiovascular death and HF hospitalization, were examined by multivariable cox models. RESULTS: Over a median follow-up of 3.4 ± 1.7 years, a total of 524 all-cause death, 334 cardiovascular deaths and 440 HF hospitalizations occurred. Compared with patients with eGFR ≥ 60 ml/min/1.73 m², those with eGFR 30-59 ml/min/1.73 m² were associated with an increased risk of the all-cause death (adjusted hazard ratio [HR], 1.47; 95% confidence interval [CI], 1.24 to 1.76; P< 0.001), cardiovascular deaths (adjusted HR, 1.53; 95% CI: 1.23 to 1.91; p < 0.001), and HF hospitalization (adjusted HR: 1.21; 95% CI: 1.00 to 1.47; p =0.049) after multivariable adjustment for potential confounders. CONCLUSIONS: eGFR 30-59 ml/min/1.73 m² was related to an increased risk of all-cause death, cardiovascular death and HF hospitalization in HFpEF patients.